2013
DOI: 10.1111/ijn.12074
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of health‐related quality of life and emotional distress among Chinese cancer survivors

Abstract: The purpose of this study is to compare health-related quality of life (HRQoL) and emotional distress among diverse cancer survivors who had completed all treatment within the previous year. A convenience sample of 353 cancers survivors (lung, head and neck, breast and prostate cancers) were recruited to complete a survey, which consisted of (i) Hospital Anxiety and Depression Scales; (ii) Chinese version of the Functional Assessment of Cancer Therapy-General version; and (iii) demographic and clinical data. T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 46 publications
0
3
0
Order By: Relevance
“…Lee et al 16 reported that quality of life in NSCLC patients was lower in comparison to healthy controls, especially when measured up to 1 year after diagnosis. A comparison of health-related quality of life among cancer survivors performed by So et al 17 suggested that lung cancer patients may experience a lower level of quality of life than patients with other types of cancers, especially in the area of functional well-being. Liao et al 18 examined a group of patients with newly diagnosed stage IIIB or stage IV lung cancer and revealed that they had a compromised global quality of life and relatively low social and role functioning at 3 months after the diagnosis of cancer.…”
Section: Discussionmentioning
confidence: 99%
“…Lee et al 16 reported that quality of life in NSCLC patients was lower in comparison to healthy controls, especially when measured up to 1 year after diagnosis. A comparison of health-related quality of life among cancer survivors performed by So et al 17 suggested that lung cancer patients may experience a lower level of quality of life than patients with other types of cancers, especially in the area of functional well-being. Liao et al 18 examined a group of patients with newly diagnosed stage IIIB or stage IV lung cancer and revealed that they had a compromised global quality of life and relatively low social and role functioning at 3 months after the diagnosis of cancer.…”
Section: Discussionmentioning
confidence: 99%
“… 41 It is common for the family to take on the responsibility of caring for the patient in China. 42 This may contribute to the patient’s ongoing unchanged HRQoL, especially because social support is a predictor of HRQoL in patients with lung cancer. 43 Our findings are consistent with other studies, in that cross-cultural differences in HRQoL exist.…”
Section: Discussionmentioning
confidence: 99%
“…Nearly half of Chinese cancer patients face serious financial problems or even cancer-related debts. 35 , 36 People with greater personal financial or family burdens are more hesitant about vaccines. 37 In the context of the mass free distribution of the COVID-19 vaccine, the rollout of the mpox vaccine must be hampered if it requires a fee.…”
Section: Discussionmentioning
confidence: 99%